Federated States of Micronesia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper examines the reasons for the poor initial performance of the Compact Trust Fund (CTF) of Micronesia and the issues related to the governance framework. The design and recent implementation of the CTF raise concerns that Micronesia will still face a difficult transition after U.S. aid ends in FY2023. The paper provides forecasts for the fund over the medium term. It also examines the business environment in Micronesia and identifies possible areas for improvement.